Evaluation of the safety and effectiveness of easyEndo™ universal stapler compared with easyEndo™ E-lite in patients submitted to gastric surgery: a retrospective/prospective study including a large number of patients - Braghetto, Italo; Czwiklitzer, Gustavo; Korn, Owen; Brante, Percy; Salinas, Macarena (International Surgery Journal, 2024)
Background: Staple line complications represent the most dangerous complication after gastric surgery. Better-formed staples could potentially reduce complications postoperatively. The newer motorized generation stapling system would lead to fewer intraoperative staple line complications compared to traditional stapling systems. Purpose was to evaluate the safety and efficacy of these two types of stapler models by determining its intraoperative performance and peri-operative complications. Methods: It was an observational cohort study including a total of 3613 patients submitted to gastric surgery for benign or malignant disease. The study was conducted within two periods: stage A using easyEndoTM universal (n=2359 patients, from January 2017 to December 2022) and stage B (n=1254 patients, from January 2023 to June 2024) using easyEndoTM E-lite motorized stapler including obese patients (n=3239), benign diseases with indication of surgical treatment (n=268) and patients with gastric cancer (n=106). Results: Although higher rate of leaks and postoperative complications were observed in patients submitted to sleeve gastrectomy or gastric bypass during stage A compared with stage B (p=0.0025), both type of staplers are safe and effective for performing gastric surgery. In patients submitted to gastric resections, no significates differences were demonstrated in terms of postoperative complications comparing the two groups (p=0.1). Conclusions: Patients operated on using motorized stapler presented less suture line interventions but no differences regarding postoperative complication. The results confirmed data published in previous reports and meta-analysis, but now including a big number of patients and complex procedures.